Resin composition, substrate, and copper-clad laminate
By developing a resin composition containing components such as naphthalene epoxy resin and bismaleimide resin, the problem of the difference between the thermal expansion coefficient of the existing resin substrate and the CTE of the semiconductor material is solved, and the CTE reduction and dimensional stability of the resin substrate are achieved.
Patent Information
- Application Number
- CN202311431886.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-23
- Filing Date
- 2023-10-31
- Publication Date
- 2025-03-25
AI Technical Summary
There is a difference in the thermal expansion coefficient of existing resin substrates and the CTE of semiconductor material silicon substrates, resulting in poor dimensional stability and difficult to meet the product stability of high requirements such as 5G communication.
By developing a resin composition, including naphthalene epoxy resin, bismaleimide resin, crosslinking agent, polysiloxane, promoter, and fillers (such as silica) to reduce its coefficient of thermal expansion, matching the CTE of the silicon substrate of the semiconductor material.
The CTE of the resin substrate is reduced to less than 3ppm/℃, or even less than 2ppm/℃, which improves the dimensional stability and thermal stability of the substrate and enhances the matching with the semiconductor material.
Smart Images

Figure BDA0004523897480000031 
Figure BDA0004523897480000041 
Figure BDA0004523897480000042
Abstract
Description
Technical Field
[0001] The present invention relates to a resin, and in particular to a resin composition, a substrate and a copper-clad laminate. Background Art
[0002] In recent years, with the development of 5G communications, copper-clad laminate materials have been developed towards the goal of higher dimensional stability and lower expansion and contraction to make the products more stable.
[0003] Furthermore, the coefficient of thermal expansion (CTE) of the current substrate is different from the coefficient of thermal expansion (CTE) of the semiconductor material silicon substrate, which is less than 2 ppm / °C, and there will be problems in material matching.
[0004] In particular, the thermal expansion coefficient of a substrate made of resin material is about 4-8 ppm / °C, which is still some distance away from the CTE of a semiconductor material silicon substrate, so there is room for improvement. Summary of the invention
[0005] The present invention provides a resin composition to reduce the CTE of a substrate and a copper-clad laminate made of the resin composition so as to better match the CTE of a semiconductor material silicon substrate and improve the dimensional stability so as to make the product have higher stability.
[0006] The resin composition of the present invention comprises naphthalene epoxy resin, bismaleimide resin, crosslinking agent, polysiloxane, accelerator and filler.
[0007] In an embodiment of the present invention, the filler comprises silicon dioxide.
[0008] In an embodiment of the present invention, based on 100 parts by weight of the resin composition, the resin composition includes 20-70% of naphthalene epoxy resin, 20-60% of bismaleimide resin, 10-20% of a cross-linking agent, 0.5-2.0 phr of polysiloxane, 0.05-1.0 phr of an accelerator; and 50-80% of a filler.
[0009] In an embodiment of the present invention, the naphthalene ring epoxy resin includes HP4710, HP9500, HP6000, NC7000L, NC7300 or a combination thereof.
[0010] In an embodiment of the present invention, the equivalent weight of the naphthalene ring epoxy resin is 170-250 g / eq.
[0011] In an embodiment of the present invention, the bismaleimide resin includes BMI1000, BMI2300, KI50P, KI70 or a combination thereof.
[0012] In an embodiment of the present invention, the polysiloxane comprises polysiloxane diamine.
[0013] In an embodiment of the present invention, the polysiloxane includes HP2000, KF8012, FM3311 or a combination thereof.
[0014] In an embodiment of the present invention, the equivalent weight of the polysiloxane is 200 to 5000 g / eq.
[0015] In an embodiment of the present invention, the silicon dioxide is spherical.
[0016] In an embodiment of the present invention, the size of the silicon dioxide is 25 nanometers to 1.5 micrometers.
[0017] In an embodiment of the present invention, the particle size of the silicon dioxide includes a large particle size, a medium particle size, a small particle size or a combination thereof.
[0018] In an embodiment of the present invention, the large particle size is 0.5-1.5 microns, the medium particle size is 0.12-0.45 microns, and the small particle size is 0.02-0.011 microns.
[0019] In an embodiment of the present invention, the resin composition may further include a siloxane coupling agent.
[0020] In an embodiment of the present invention, the siloxane coupling agent is present in an amount of 0.1 to 5 phr.
[0021] In an embodiment of the present invention, the coefficient of thermal expansion (CTE) of the resin composition is less than 3 ppm / °C.
[0022] In an embodiment of the present invention, the coefficient of thermal expansion (CTE) of the resin composition is less than 2 ppm / °C.
[0023] The present invention also provides a substrate, comprising any one of the above-mentioned resin compositions.
[0024] The present invention also provides a copper clad laminate, comprising a first copper foil, a second copper foil, a glass fiber cloth located between the first copper foil and the second copper foil, and a resin, wherein the resin is formed by the above-mentioned resin composition and is located in the glass fiber cloth.
[0025] In another embodiment of the present invention, the glass fiber cloth includes E-glass and S-glass.
[0026] In another embodiment of the present invention, the resin can be formed in the glass fiber by impregnating the glass fiber cloth with the resin composition and then baking the glass fiber.
[0027] Based on the above, the resin composition, substrate and copper clad laminate provided by the present invention have a lower CTE, which can achieve an effect of less than 3ppm / ℃, or even less than 2ppm / ℃. They have better material matching with the semiconductor material silicon substrate with a CTE of less than 2ppm / ℃, and have higher heat resistance, better thermal stability, higher dimensional stability and other characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] none. DETAILED DESCRIPTION
[0029] The following will describe the embodiments of the present invention in detail. However, these embodiments are illustrative only and the present invention is not limited thereto.
[0030] The resin composition of the present invention includes naphthalene ring epoxy resin, bismaleimide resin, crosslinking agent, polysiloxane, accelerator and filler, and may further include siloxane coupling agent to provide a resin with high dimensional stability. The above components will be described in detail below.
[0031] Naphthalene epoxy resin
[0032] The naphthalene ring epoxy resin may include HP4710, HP9500, HP6000, NC7000L, NC7300 or a combination thereof, and its structure and equivalent weight are listed in the following Table 1, wherein the presence of two benzene rings can improve its heat resistance and make the resin more stable at high temperatures.
[0033] Based on 100 parts by weight of the resin composition, the resin composition comprises 20-70% of naphthalene epoxy resin, and the equivalent weight of the naphthalene epoxy resin is 170-250 g / eq.
[0034] [Table 1]
[0035]
[0036]
[0037] Bismaleimide resin
[0038] One of the purposes of adding bismaleimide resin is to improve the thermal stability of the resin as a whole. The bismaleimide resin may include BMI1000, BMI2300, KI50P, KI70 or a combination thereof, and its structure and melting point are listed in Table 2 below.
[0039] Based on 100 parts by weight of the resin composition, the resin composition includes 20-60% of bismaleimide resin.
[0040] [Table 2]
[0041]
[0042]
[0043] Crosslinking agent
[0044] Based on 100 parts by weight of the resin composition, the resin composition includes 10-20% of a cross-linking agent.
[0045] Polysiloxane
[0046] Polysiloxane is a long-chain siloxane, including polysiloxanediamine. Polysiloxane may include HP2000, KF8012, FM3311 or a combination thereof, and its structure and equivalent weight are listed in Table 3 below, wherein HP2000 is a three-dimensional structure, while KF8012 and FM3311 are linear. Its special microstructure is used to promote the dispersion of raw materials and reduce the thermal expansion coefficient CTE of the substrate to below 3ppm / ℃, or even below 2ppm / ℃, so that the resin has high dimensional stability.
[0047] Based on 100 parts by weight of the resin composition, the resin composition comprises 0.5 to 2 phr of polysiloxane, and the equivalent weight of the polysiloxane is 200 to 5000 g / eq.
[0048] [Table 3]
[0049]
[0050]
[0051] As shown in Table 3 above, the structures of HP2000, KF8012, and FM3311 all have a functional group -NH2, which can react with the epoxy structure of the naphthalene epoxy resin or the double bond structure of the BMI resin to improve the thermal stability of the resin after the reaction and reduce its CTE; and these polysiloxanes can also be regarded as hardeners, and their long chain structures can improve the dispersion of fillers, such as silica, in the resin.
[0052] Accelerator
[0053] Based on 100 parts by weight of the resin composition, the resin composition includes 0.05 phr to 1.0 phr of an accelerator to help the reaction proceed.
[0054] filler
[0055] The filler includes silicon dioxide. The silicon dioxide is spherical. The size of the silicon dioxide is 25 nanometers to 1.5 micrometers. The particle size of the silicon dioxide includes a large particle size, a medium particle size, a small particle size or a combination of particle sizes. The particle size is adjusted as required, for example, to achieve a higher packing density, two or three of the large particle size, the medium particle size and the small particle size are selected. The large particle size is about 0.5 to 1.5 micrometers, the medium particle size is about 0.12 to 0.45 micrometers, and the small particle size is about 0.02 to 0.011 micrometers.
[0056] Based on 100 parts by weight of the resin composition, the resin composition comprises 50 to 80% of filler.
[0057] Siloxane coupling agent
[0058] In addition to the above-mentioned naphthalene epoxy resin, bismaleimide resin, crosslinking agent, polysiloxane, accelerator and filler, the present invention may also include a siloxane coupling agent, which can increase the dispersibility between the raw materials like polysiloxane and can also enhance the adhesion between the resin and the copper foil after the reaction. Based on 100 parts by weight of the resin composition, the resin composition includes 0.1 to 5 phr of the siloxane coupling agent.
[0059] substrate
[0060] The resin formed by using the aforementioned resin composition can be used to form a substrate.
[0061] Copper Clad Laminate
[0062] The resin formed by the resin composition can be used in a copper clad laminate. The copper clad laminate includes a first copper foil, a second copper foil, a glass fiber cloth located between the first copper foil and the second copper foil, and a resin, wherein the resin is formed by the resin composition and located on the glass fiber cloth.
[0063] The above-mentioned glass fiber cloth may include glass fiber cloths with different properties such as E-glass and S-glass.
[0064] The resin formed by the aforementioned resin composition and located in the glass fiber cloth can be formed by dipping the glass fiber cloth in the aforementioned resin composition and then treating it by baking or the like to form the resin in the glass fibers.
[0065] Preparation method
[0066] Firstly, the resin composition, including naphthalene epoxy resin, bismaleimide resin, crosslinking agent, polysiloxane, accelerator and filler, is stirred and mixed, and dispersed and mixed using high-speed homogenizing equipment when necessary to obtain a formula solution.
[0067] The glass fiber cloth is then immersed in the formulated solution and then processed by baking or the like.
[0068] Then, the glass fiber cloth impregnated with the formula solution is combined with the copper foil and subjected to heat pressing to obtain a copper foil substrate.
[0069] Finally, the copper foil is removed by chemical method to obtain a substrate made of the resin composition disclosed by the present invention.
[0070] Examples and Comparative Examples
[0071] The present invention uses the following resin composition ratios and the substrates made by the above-mentioned preparation method for different experimental subjects to carry out the series of characteristic analysis tests listed in the following tables.
[0072] First, please refer to Table 4 below, and conduct the following tests on naphthalene epoxy resin, BPA epoxy resin, and BPF epoxy resin.
[0073] [Table 4]
[0074]
[0075] The structures and equivalent weights of BPA epoxy resin and BPF epoxy resin are shown in Table 5 below.
[0076] [Table 5]
[0077]
[0078]
[0079] The results in Table 4 show that the CTE of Example 1 using the naphthalene ring epoxy resin is 2.6 ppm / °C, which is not only lower than the CTE (5.3 ppm / °C) of the BPA epoxy resin in Comparative Example 1 and the CTE (5.1 ppm / °C) of the BPF epoxy resin in Comparative Example 2, but also lower than the 4-8 ppm / °C thermal expansion coefficient of the substrate made of the current resin material, and is more compatible with the CTE of the semiconductor material silicon substrate. It is obvious that the naphthalene ring epoxy resin has better performance than the BPA epoxy resin and the BPF epoxy resin.
[0080] Referring to Table 6 below, the following tests were conducted on the effect of the presence of polysiloxane and different polysiloxanes.
[0081] [Table 6]
[0082]
[0083] In Table 6, Examples 1 to 4 have the same formula ratio except for polysiloxane; Example 1 has no polysiloxane, and Examples 2 to 4 have 6.25 g of polysiloxane, which are HP2000, KF8012, and FM3311, respectively.
[0084] The results in Table 6 show that the CTE of Example 1 is 2.6 ppm / °C, which is lower than the 4-8 ppm / °C thermal expansion coefficient of substrates made of existing resin materials and is more compatible with the CTE of semiconductor material silicon substrates.
[0085] In addition, the CTEs of Examples 2 to 4 with polysiloxane are 1.8 ppm / °C, 1.9 ppm / °C, and 1.9 ppm / °C, respectively, all of which are less than 2 ppm / °C. They are lower than the CTE of Example 1 without polysiloxane and are closer to the CTE of the semiconductor material silicon substrate, thus having a better effect.
[0086] Please refer to Table 7 below for the following tests performed on different naphthalene ring epoxy resins.
[0087] [Table 7]
[0088]
[0089] In Table 7, Examples 5 to 9 have the same formulation ratio except that different naphthalene ring epoxy resins are used; the naphthalene ring epoxy resins used in Examples 2 to 6 are HP4710, HP9500, HP6000, NC7000L, and NC7300, respectively.
[0090] The results in Table 7 show that the CTE of Examples 5 to 9 are 2.6ppm / °C, 2.8ppm / °C, 2.7ppm / °C, 2.9ppm / °C, and 2.8ppm / °C, respectively, which are lower than the 4-8ppm / °C thermal expansion coefficient of substrates made of current resin materials, and are more compatible with the CTE of semiconductor material silicon substrates.
[0091] Please refer to Table 8 below for the following tests performed on different bismaleimide resins.
[0092] [Table 8]
[0093]
[0094] In Table 8, Examples 10 to 13 have the same formulation ratio except that the bismaleimide resins used are different; the bismaleimide resins used in Examples 10 to 13 are BMI1000, BMI2300, KI50P, and KI70, respectively.
[0095] The results in Table 8 show that the CTE of Examples 10 to 13 are 2.9ppm / °C, 2.8ppm / °C, 2.7ppm / °C, and 2.8ppm / °C, respectively, which are lower than the 4-8ppm / °C thermal expansion coefficient of substrates made of current resin materials, and are more compatible with the CTE of semiconductor material silicon substrates.
[0096] Please refer to Table 9 below for the following tests on different fiberglass cloths.
[0097] [Table 9]
[0098]
[0099]
[0100] In Table 9, Comparative Examples 3 and 4 have the same formulation ratio except that the types of glass fiber cloth used are different.
[0101] The results in Table 9 show that the CTE of Comparative Examples 3 and 4 are 5.6 ppm / °C and 2.6 ppm / °C, respectively, which are lower than the 4-8 ppm / °C thermal expansion coefficient of substrates made of current resin materials, and are more compatible with the CTE of semiconductor material silicon substrates.
[0102] In summary, the resin composition, substrate and copper-clad laminate provided by the present invention have a lower CTE, which can achieve an effect of less than 3ppm / ℃, or even less than 2ppm / ℃. They have better material matching with the semiconductor material silicon substrate with a CTE of less than 2ppm / ℃, and have higher heat resistance, better thermal stability, higher dimensional stability and other characteristics.
Claims
1. A resin composition, characterized in that: include: Naphthalene epoxy resin; Bismaleimide resin; Cross-linking agent; Polysiloxane; Accelerators; as well as filler.
2. The resin composition according to claim 1, characterized in that The filler comprises silicon dioxide.
3. The resin composition according to claim 1, characterized in that Based on 100 parts by weight of the resin composition, the resin composition comprises: 20-70% naphthalene epoxy resin; 20-60% bismaleimide resin; 10-20% cross-linking agent; 0.5-2.0 phr of polysiloxane; 0.05 phr to 1.0 phr of an accelerator; and 50-80% filler.
4. The resin composition according to claim 1, characterized in that The naphthalene ring epoxy resin includes HP4710, HP9500, HP6000, NC7000L, NC7300 or a combination thereof.
5. The resin composition according to claim 1, characterized in that The equivalent weight of the naphthalene ring epoxy resin is 170 to 250 g / eq.
6. The resin composition according to claim 1, characterized in that The bismaleimide resin includes BMI1000, BMI2300, KI50P, KI70 or a combination thereof.
7. The resin composition according to claim 1, characterized in that The polysiloxane comprises polysiloxane diamine.
8. The resin composition according to claim 1, characterized in that The polysiloxane comprises HP2000, KF8012, FM3311 or a combination thereof.
9. The resin composition according to claim 1, characterized in that The equivalent weight of the polysiloxane is 200 to 5000 g / eq.
10. The resin composition according to claim 2, characterized in that The silicon dioxide is spherical.
11. The resin composition according to claim 2, characterized in that: The size of the silicon dioxide is 25 nanometers to 1.5 micrometers.
12. The resin composition according to claim 2, characterized in that: The particle size of the silicon dioxide includes a large particle size, a medium particle size, a small particle size or a combination thereof.
13. The resin composition according to claim 12, characterized in that The large particle size is 0.5 to 1.5 microns, the medium particle size is 0.12 to 0.45 microns, and the small particle size is 0.02 to 0.011 microns.
14. The resin composition according to claim 1, characterized in that Siloxane coupling agents may also be included.
15. The resin composition according to claim 14, characterized in that The siloxane coupling agent is 0.1-5 phr.
16. The resin composition according to claim 1, characterized in that The thermal expansion coefficient (CTE) of the resin composition is less than 3 ppm / °C.
17. A substrate, characterized in that: The invention comprises the resin composition according to any one of claims 1 to 16.
18. A copper-clad laminate, characterized in that: include: First copper foil; Second copper foil; Glass fiber cloth, located between the first copper foil and the second copper foil; as well as The resin is formed from the resin composition according to any one of claims 1 to 16 and is located on the glass fiber cloth.
19. The copper-clad laminate according to claim 18, characterized in that: The glass fiber cloth includes E-glass and S-glass.
20. The copper clad laminate according to claim 18, characterized in that: The resin can be formed on the glass fiber by impregnating the glass fiber cloth with the resin composition and then baking the resin.